Back to the roots - dermatology in ancient Egyptian medicine - Hartmann, Arndt (Journal der Deutschen Dermatologischen Gesellschaft, 2016)
Although ancient Greek and Roman medicine is generally considered the origin of European medicine, there is evidence in ancient Egyptian texts suggesting a precursor role of ancient Egyptian medicine in this regard. What did Greek and Roman physicians learn from their Egyptian counterparts? Of the medical papyri discovered to date, the largest and most significant - the Ebers papyrus and the Smith papyrus - originate from the beginning of the New Kingdom, however, they were - at least in part - already written during the Old Kingdom. Considering the times, the spectrum of diseases treated as well as the range of conservative and surgical treatment methods was truly astounding. Taking a medical history, performing a thorough manual examination, and assessing clinical findings constituted key components in establishing a diagnosis. Apart from hygienic aspects, skin and hair disorders, the treatment of acute and chronic wounds and injuries as well as cosmetic procedures took on an important role. Even back then, physicians sought to assess inflammatory processes with respect to their cardinal features, implement graded wound therapy, and treat diseases with allopathic drugs. The 'channel theory' prevalent at that time, in which the unimpeded flow of bodily fluids was considered a fundamental prerequisite for health, may likely be regarded as precursor of ancient Greek humoral pathology. The latter became the basis for the subsequently established theory of the four humors, and was thus essential for the entire field of medieval medicine.
EVALuna:33697